Severe rhabdomyolysis in an infant with Multisystem Inflammatory Syndrome Related to COVID-19 (MIS-C) - Valdivia-Tapia, María del Carmen (2023)
A case of severe rhabdomyolysis associated with multisystem inflammatory syndrome related to COVID-19 (MIS-C) is presented in a one-year 10-month-old boy who presented digestive symptoms, myalgia, weakness, fever, and dark urine. COVID-19 IgM (-) IgG (+) serological test, COVID-19 PCR negative. Initial creatine kinase (CK) presented non-dosable values, with the highest reported level being 517,600 U/L. The creatinine value remained normal throughout the hospitalization. He received human immunoglobulin 2 g/Kg, Methylprednisolone 10 mg/Kg/d, and acetylsalicylic acid to manage MIS-C. Aggressive hydration and urine alkalinization were provided to manage rhabdomyolysis. Positive evolution with discharge after ten days. Few reported cases of rhabdomyolysis are associated with MIS-C and none with such high CK values. Based on the possible complications, performing CK dosing in all patients with MIS-C is suggested routinely.